Structural, Magnetic and Electrical Properties and Colossal Magnetoresistive Effect Of La0.67Sr0.33mno3 Perovskites With Dy Substitution At La Site - Lee, Oon Jew (2007)
A thorough study on structural, magnetic and electrical properties and colossal magnetoresistive (CMR) effect in La0.67Sr0.33MnO3 or generically known as LSMO manganites substituted with dysprosium (Dy) at lanthanum (La) site is the main area of research in this thesis. In the first part of this work, the samples of (La1-xDyx)0.67Sr0.33MnO3 (LDSMO) with x=0.00-0.90 were synthesized using standard solid state reaction method. The second part involves the characterization of the samples using X-ray Diffractometer (XRD), Vibrating Sample Magnetometer (VSM), four point probe electrical resistivity and magnetoresistance measurement system, and Atomic Force Microscope (AFM). The XRD pattern for all samples reveals a single phase pattern with rhombohedral structure. When Dy concentration increases, the magnetization value at any given temperature decreases markedly. Moreover, the magnetization (temperature dependence of magnetization and isothermally hysteresis loop) show a prominent transition corresponding to Curie temperature,TC arising from long range ferromagnetic order to a short range nature with paramagnetic order (0.00≤≤x0.06), antiferromagnetic (x=0.90) and spin glass state (x=0.80). The electrical resistivity increases with the shifting of metal-insulator transition temperature, TMIT to lower temperature. Low temperature resistivity datas signify that the resistance of electrical transport mechanism in the metallic region can be ascribed as electron-electron scattering with minor attribution of magnon-electron scattering. On the other hand, the high temperature resistivity data satisfy the variable range hopping (VRH) model and small polaron hopping (SPH) model. The considerable change in the density of states at Fermi level, N(Ef) and activation energy, Ea which was obtained from fitting the electrical transport data, proved that the mobility of the electron decreases proportionally with Dy concentration. The N(Ef) values were found within the range of 1.53x1016 eV-1cm-3 to 1.45x1018 eV-1cm-3 whereas the Ea values were ranged from 2.96x102 meV to 1.32x103 meV. The TC-TMIT discrepancy is due to the fact that the former is an intrinsic characteristic, the latter depends strongly on the extrinsic factor e.g. grain size (grain boundary). The effect of grain size on the CMR mechanism is analyzed from AFM images. The grain size was found to decrease exponentially from 2.88 μm (x=0.00) to 1.34 μm (x=0.90) with the increase of Dy concentration. As the grain size decreases, the ratio of surface over volume increased. Hence, the influence of grain boundaries effect cannot be excluded and eliminated in all samples. Overall, negative CMR in ascending order had been obtained in all samples as decreasing temperature at low magnetic field. This phenomenon is known as Low Field Magnetoresistance (LFMR). Spin dependent scattering, spin polarization and tunneling between neighbouring grains and the magnetically disordered grain boundaries seems to be responsible for the LFMR effect. The highest CMR value with 62.2% is obtained in x=0.60 LDySMO sample at 90K.